Sex-related differences in clinical outcomes and predictive factors in the very elderly patients with ACS undergoing PCI - Jia-li Wang; Xiao-quan He; Chun-yan Guo; Hui Chen; Hong-wei Li; Hong-wei Li; Hong-wei Li; Shu-mei Zhao (Frontiers in Cardiovascular Medicine, 2022)
BackgroundAs shown in previous studies, there may be sex-related differences in clinical outcomes in patients with acute coronary syndromes (ACS) after percutaneous coronary intervention (PCI). However, the benefits of PCI in very elderly ACS patients and the gender differences were poorly described and understood. We investigated the clinical characteristics and outcomes after PCI by sex stratification, and the predictive factors of major adverse cardiovascular and cerebrovascular events (MACCE) in this very elderly ACS cohort.MethodsA total of 1,676 consecutive ACS patients (50.2% women) aged ≥80 years old between January 2013 and May 2020 were recruited in this study. All patients were divided into four groups according to gender and treatment: male PCI (n = 321) and conservative management groups (n = 513), and female PCI (n = 283) and conservative management groups (n = 559). Clinical and coronary lesion characteristics were compared among four groups, also the clinical outcomes. MACCE and their predictive factors were assessed using Kaplan–Meier curve and Cox regression analysis.ResultsPCI procedures were conducted in 604 patients, and 1,072 were conservative management. Men were most likely to present with prior myocardial infarction (MI), peripheral artery disease, and chronic total occlusion (CTO); women had a higher prevalence of hypertension and dyslipidemia. The proportion of men receiving PCI procedures was significantly higher than that of women (38.5 vs. 33.6%, p = 0.038). Compared to conservative management, successful PCI significantly improved composite MACCE in both men (33.9 vs. 18.4%, p < 0.001) and women (27.9 vs. 20.8%, p = 0.026). There were no differences between sex in the improvement of clinical outcomes after PCI. In addition, age, ST-segment elevation myocardial infarction (STEMI), log N-terminal pro-brain natriuretic peptide (NT-proBNP), P2Y12 receptor antagonist, and β-blocker were independently associated with the incidence of MACCE after PCI tested by the Cox regression model, but not gender (male: hazard ratio (HR) 1.275, 95% confidence interval (CI) 0.853–1.905, p = 0.236).ConclusionIn this very elderly ACS cohort, men presented with more complex clinical conditions, and women were less likely to receive PCI treatment. Both women and men had similar benefits from the PCI procedure in the decrease of MACCE.